Study on Heat Treatment of Mg-8Gd-5Y-2Zn-0.5Zr Alloy Under High Magnetic Fields - FANG Can-feng MIAO Run-qi MENG Ling-gang HAO Hai ZHANG Xing-guo (钢铁研究学报：英文版, 2012)
The heat treatment microstructures and XRD patterns of the Mg-8Gd-5Y-2Zn-0.5Zr(wt.%)alloy in the absence and presence of a 10T high magnetic field have been investigated.The investigations show that the grains of a-Mg demonstrate a preferred orientation due to the magnetic driving force.In addition,high magnetic fields can promote the growth of the long period ordered structure(LPS)phase to the grain interior.And the corresponding mechanisms are also discussed in this article.